Evaluating the Long-Run Dynamics of Inflation, Unemployment, and Exchange Rates on Economic Growth: An Econometric Analysis of Time Series Data from Bangladesh with Verification of Okun’s Law - Islam, Md Aminul; Khatun, Amina; Haque, Md Obidul (South Asian Journal of Social Sciences and Humanities, 2025)
The foreign exchange rate, jobless rate, rate of inflation, and real GDP have always been  considered to be the most burning issues for the world. This study seeks to analyze the effects  of exchange rates, unemployment rates, and price levels on real GDP from 1991 to 2023,  utilizing time series statistical methods. The research utilized sophisticated econometric  techniques to analyze the findings. The series' stationary properties were initially assessed  using the Augmented Dickey-Fuller unit root test. The Johansen co-integration approach  determines the variables' long-term relationship. Granger casualty test was used to determine  factor causal linkages. The empirical findings from the cointegration test indicate that, over the  long term, both the exchange rate and the inflation rate exert a significant positive influence on  the real gross domestic product (RGDP) in Bangladesh. On the contrary, the unemployment  rate adversely affects real Gross Domestic Product (RGDP) in Bangladesh, this signifies that why Okun’s Law has the existence in Bangladesh. The findings from the vector error correction  model (VECM) suggest that inflation and unemployment are expected to reach equilibrium  following a period of error correction; however, the exchange rate and real GDP show minimal  significant adjustment towards achieving long-run equilibrium. The results of the Granger test  indicate a bilateral causal relationship between unemployment and the exchange rate. The  findings derived from the impulse response function show that in a very few cases the external  shocks have been neutralized for a certain period of time but in most cases the external shocks  have not been neutralized.
Keywords: RGDP; Exchange Rate; Unemployment Rate; Inflation Rate; ADF; Co-integration; VECM; Impulse Response